DEAD-Box Helicase DDX6 Facilitated RIG-I-Mediated Type-I Interferon Response to EV71 Infection - Zhang, Rui; Cheng, Min; Liu, Bingxin; Yuan, Meng; Chen, Deyan; Wang, Yujiong; Wu, Zhiwei (Frontiers in Cellular and Infection Microbiology, 2021)
Previous studies have shown that DEAD (Glu-Asp-Ala-Glu)-box RNA helicases play important roles in viral infection, either as cytosolic sensors of viral nucleic acids or as essential host factors for viral replication. In the current study, we found that DDX6, a DEAD-box RNA helicase and a P-body component, exhibited anti-Enterovirus 71 activity through augmenting RIG-I-mediated type-I IFN response. Moreover, DDX6 binds viral RNA to form an RNA-protein complex to positively regulate the RIG-I-mediated interferon response; however, EV71 has evolved a strategy to antagonize the antiviral effect of DDX6 by proteolytic degradation of the molecule through its non-structural protein 2A, a virus encoded protease.